Botanical identity of a medicinal root commercialized under the name "Santa Lucía Morotí" and anatomical, micrographic, and histochemical characterization - Gaeta, Nadia Antonela; Agudelo, Ignacio Jorge; Anconatani, Leonardo Martín; Ricco, Rafael Alejandro (Ethnobotany Research and Applications, 2024)
Background: Traditional medicine in Paraguay relies on various medicinal plants referred to as santa lucía morotí in the vernacular. These plants have many uses, from treating ophthalmic conditions to serving as a refreshing remedy. This study aims to identify the botanical species associated with the plant material sold under the name santa lucía morotí in informal markets within the Ciudad Autónoma de Buenos Aires, República Argentina. This investigation aims to determine if there has been a substitution of this plant material with a local species and to establish anatomical, micrographic, and histochemical parameters. Methods: Fresh roots were procured from street vendors within the Paraguayan community residing in the Ciudad Autónoma de Buenos Aires, República Argentina, labeled as santa lucía morotí. These roots were cultivated until the plants reached the flowering stage, at which point they were identified using taxonomic keys. Transverse sections were prepared and stained with safranin and fast green. Additionally, histochemical reactions were conducted to localize and characterize families of metabolites, with a known variety of biological and pharmacological activities. Results: The plant was identified as Commelina platyphylla Klotzsch ex Seub. (Commelinaceae). This suggests that there has been no substitution of this plant material. Terpenoids, saponins, alkaloids, and flavonoids were successfully histochemical localized. Conclusions: The species under investigation has not been replaced as it transitioned from traditional Paraguayan medicine to the urban environment of Buenos Aires City. The characterization of metabolites provides valuable guidance for phytochemical and pharmacological research to validate ethnomedical uses. Keywords: Santa Lucía Morotí, Commelina platyphylla, urban ethnomedicine, migrant ethnomedicine